KOMUNIKASI ANTARBUDAYA DALAM ISLAM DAN INTERKULTURALISME: STUDI KRITIS TANTANGAN MULTIKULTURAL DI ERA GLOBAL - Miftahul Khoirin; Khusnul Khotimah; Nawawi Nawawi (Halaqah: Journal of Multidisciplinary Islamic Studies, 2026)
The dynamics of interaction in multicultural societies in the era of globalization are often characterized by tensions arising from differences in symbolic codes and cultural perceptions. Communication and culture are two constitutive entities; however, differences in background frequently lead to misunderstandings, stereotypes, and ethnocentrism, particularly in the Indonesian context, which is marked by high ethnic diversity. This study examines intercultural communication from the perspectives of interculturalism and Islamic ethics within the dynamics of multicultural societies in the era of globalization. It is grounded in the increasing issues of misunderstanding, stereotypes, and ethnocentrism resulting from differences in culture, language, and systems of meaning in social interaction. This research employs a qualitative approach using library research through critical analysis of literature on intercultural communication, interculturalism, and Islamic communication ethics. The findings show that intercultural communication cannot be understood merely as a technical competence, but as a process involving cultural awareness, contextual sensitivity, and an ethical framework. The integration of modern intercultural communication theory with Islamic values such as ta’aruf, tasamuh, tabayyun, as well as qaulan sadīda and qaulan layyina produces an Islamic intercultural communication model with an integrative character. The model consists of three layers: cultural competence, contextual awareness, and Islamic ethics as a normative foundation. This study emphasizes that intercultural communication should be understood as a social practice containing ethical and spiritual dimensions in building harmony within multicultural societies.